2018
DOI: 10.1111/tpj.14021
|View full text |Cite
|
Sign up to set email alerts
|

Subdiffraction‐resolution live‐cell imaging for visualizing thylakoid membranes

Abstract: The chloroplast is the chlorophyll-containing organelle that produces energy through photosynthesis. Within the chloroplast is an intricate network of thylakoid membranes containing photosynthetic membrane proteins that mediate electron transport and generate chemical energy. Historically, electron microscopy (EM) has been a powerful tool for visualizing the macromolecular structure and organization of thylakoid membranes. However, an understanding of thylakoid membrane dynamics remains elusive because EM requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 53 publications
5
33
1
Order By: Relevance
“…The mutants stn8 and pbcp show an altered organization of thylakoid membranes. In stn8 , and particularly in the double mutant stn7stn8 , the diameter of the thylakoid grana is larger compared to the wild type (Fristedt et al 2009, Iwai et al 2018, Nath, et al 2013). In contrast in the pbcp phosphatase mutant, the diameter of the grana is similar to the wild type, but the number of membrane layers in grana stacks is reduced (Samol, et al 2012).…”
Section: Introductionmentioning
confidence: 94%
“…The mutants stn8 and pbcp show an altered organization of thylakoid membranes. In stn8 , and particularly in the double mutant stn7stn8 , the diameter of the thylakoid grana is larger compared to the wild type (Fristedt et al 2009, Iwai et al 2018, Nath, et al 2013). In contrast in the pbcp phosphatase mutant, the diameter of the grana is similar to the wild type, but the number of membrane layers in grana stacks is reduced (Samol, et al 2012).…”
Section: Introductionmentioning
confidence: 94%
“…Both in vivo and in vitro studies have indicated a decrease in grana diameter and the total area of appressed membranes under red or blue light, i.e. when both the PSII core and LHCII become phosphorylated (Chuartzman et al, 2008;Iwai et al, 2018). However, a similar decrease in appressed thylakoid area was observed in dark-acclimated plants exposed directly to high light (HL; Khatoon et al, 2009;Herbstová et al, 2012) when there is high PSII core phosphorylation but complete dephosphorylation of LHCII (Tikkanen et al, 2008a).…”
mentioning
confidence: 95%
“…individual chloroplasts and higher). In addition to FLIM, 3D structural illumination microscopy (3D‐SIM) offers interesting opportunities for studying chloroplast ultrastructures in intact cells (Iwai et al ., ). Although the resolution of this fluorescence‐based technique is lower than EM, it is highly complementary to EM‐based techniques (that monitor only snapshots in time of fixed samples) because it allows in vivo studies on chloroplast dynamics in real time.…”
Section: New Techniques – Better Insightsmentioning
confidence: 99%